Heme in Cardiovascular Diseases: A Ubiquitous Dangerous Molecule Worthy of Vigilance - Guo, Yuyang; Zhao, Hengli; Lin, Zhibin; Ye, Taochun; Xu, Dingli; Zeng, Qingchun (Frontiers in Cell and Developmental Biology, 2022)
Heme, the protoporphyrin IX iron complex is widely present in the human body and it is involved in oxygen storage, electron transfer, and enzymatic reactions. However, free heme can be toxic as it catalyzes the production of reactive oxygen species, oxidizes lipids and proteins, and causes DNA damage, thereby inducing a pro-inflammatory environment. The generation, metabolism, and degradation of heme in the human body are regulated by precise mechanisms to ensure that heme remains non-toxic. However, in several types of cardiovascular diseases, impaired metabolism and exposure to heme may occur in pathological processes, including neovascularization, internal hemorrhage, ischemia, and reperfusion. Based on years of research, in this review, we aimed to summarize the underlying mechanisms by which heme contributes to the development of cardiovascular diseases through oxidative stress, relative pathway gene expression regulation and phenotypic changes in cells. Excess heme plays a detrimental role in atherosclerosis, heart failure, myocardial ischemia-reperfusion injury, degenerative aortic valve stenosis, cardiac iron overload. Recent researches revealed that in some cases heme involved in cardiac damage though ferroptosis. Thus, heme concentrations beyond normal levels are dangerous. Further research on the role of heme in cardiovascular diseases is needed.